Whites' opposition to busing symbolic racism or realistic group conflict? - Bobo, Lawrence (1983)
The theory of symbolic racism contends that whites' opposition to busing springs from a basic underlying prejudiced or intolerant attitudinal predisposition toward blacks, not self-interest or realistic group conflict motives do help explain whites' opposition to busing. Two major criticisms of the symbolic racism approach are made: (a)that the tests of symbolic racism versus group conflict explanations of opposition to busing have not been fair because of a narrow definition of group interests that ignores the role of subjectively appreciated threat and challenges to group status; and (b) that by forcing racial attitudes onto a single continuum running from prejudice to tolerance, the symbolic racism researchers overlook the importance of the perception that the civil rights movement is a threatening force. By reanalyzing the Michigan National Election study data used by Sears, Hensler, and Speer (1979) and Sears, Lau, Tyler, and Allen (1980), the present research broadens the notion of self-interest and operates with a multidimensional conceptualization of racial attitudes and in so doing demonstrates that whites' opposition to busing reflects group conflict motives, not simply a new manifestation of prejudice.